1994
DOI: 10.1021/jm00049a015
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclic Quinoxalinediones: 5,6-Dihydro-1H-pyrrolo[1,2,3-de]quinoxaline-2,3-diones and 6,7-Dihydro-1H,5H-pyrido[1,2,3-de]quinoxaline-2,3-diones as Potent Antagonists for the Glycine Binding Site of the NMDA Receptor

Abstract: A series of tricyclic quinoxalinediones, 5,6-dihydro-1H-pyrrolo[1,2,3-de]quinoxaline-2,3-diones and 6,7-dihydro-1H,5H-pyrido[1,2,3-de]quinoxaline-2,3-diones, were synthesized and was evaluated for their affinity for the glycine binding site of the NMDA receptor using a [3H]-5,7-dichlorokynurenic acid binding assay. The six-membered ring-fused tricyclic quinoxalinedione 18g (Ki = 9.9 nM) displayed high affinity for the glycine site. The anilide derivative 20g (Ki = 2.6 nM) was 4-fold more potent than 18g and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 6 publications
4
34
0
Order By: Relevance
“…Based upon these observations, much e¤ort has been devoted to developing new classes of drugs designed to block NMDA receptor activity but lacking the disturbing psychotomimetic side e¤ects. A promising approach in this respect has been the synthesis of novel NMDA / glycine site antagonists which not only display high a¦nity for the NMDA / glycine regulatory site at the NMDA receptor but also have been shown to be potent inhibitiors of various NMDA receptor-mediated functional responses in vitro (Leeson and Iversen 1994;Nagata et al 1994;Keana et al 1995;Kehne et al 1995;Woodward et al 1995;Priestley et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based upon these observations, much e¤ort has been devoted to developing new classes of drugs designed to block NMDA receptor activity but lacking the disturbing psychotomimetic side e¤ects. A promising approach in this respect has been the synthesis of novel NMDA / glycine site antagonists which not only display high a¦nity for the NMDA / glycine regulatory site at the NMDA receptor but also have been shown to be potent inhibitiors of various NMDA receptor-mediated functional responses in vitro (Leeson and Iversen 1994;Nagata et al 1994;Keana et al 1995;Kehne et al 1995;Woodward et al 1995;Priestley et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The arrival of novel, systemically active NMDA / glycine antagonists is now rapidly changing the situation (Leeson and Iversen 1994;Nagata et al 1994;Keana et al 1995). Furthermore, there is evidence to suggest that the novel, systemically active, NMDA / glycine site antagonists possess anticonvulsant and neuroprotective properties (Leeson et al 1994;Bristow et al 1996b;Ilyin et al 1996;Kotlinska and Liljequist 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of (R)-angustureine (1) begins with the preparation of (S)-β-amino ester 3 by enzymatic kinetic resolution of racemic 3. 4 The material thus obtained was subjected to a three-step annulation sequence to dihydropyridone (DHPD) triflate 5: acylation of secondary amine 3, Reformatsky-type cyclocondensation, and enol triflation (3+45) (Scheme 2). This annulation sequence is conveniently conducted without purification of intermediates to afford 5 in 72% overall yield.…”
Section: Resultsmentioning
confidence: 99%
“…The N4-C5 bridged derivatives were extensively studied, [274][275][276][277][278] but most of them showed to be more selective for the Gly/NMDA receptor site than the AMPA ones. For example, SM18400 (35, Fig.…”
Section: (Hetero)cyclic-fused Quinoxalinone Derivativesmentioning
confidence: 99%
“…276 The studies reported on this series of compounds have been useful in clarifying the selectivity requirements for the AMPA and Gly/NMDA receptors. [276][277][278] The tricyclic C3-N4 bridged compounds were designed starting from the structural requirements suggested by reported AMPA pharmacophore models 45,225,242 and with the aim of improving physicochemical properties that characterized most of the quinoxaline-2,3-dione derivatives. In fact, the low-water solubility was in part attributed to the presence of the 2,3-dione moiety.…”
Section: (Hetero)cyclic-fused Quinoxalinone Derivativesmentioning
confidence: 99%